Novel Zinc-Related Differentially Methylated Regions in Leukocytes of Women With and Without Obesity - Noronha, Natália Yumi; Barato, Mariana; Sae-Lee, Chanachai; Pinhel, Marcela Augusta de Souza; Watanabe, Lígia Moriguchi; Pereira, Vanessa Aparecida Batista; Rodrigues, Guilherme da Silva; Morais, Déborah Araújo; de Sousa, Wellington Tavares; Souza, Vanessa Cristina de Oliveira; Plaça, Jessica Rodrigues; Salgado, Wilson; et al. (Frontiers in Nutrition, 2022)
Introduction: Nutriepigenetic markers are predictive responses associated with changes in human “surrounding” environmental conditions, which may influence metabolic diseases. Although rich in calories, Western diets could be linked with the deficiency of micronutrients, resulting in the downstream of epigenetic and metabolic effects and consequently in obesity. Zinc (Zn) is an essential nutrient associated with distinct biological roles in human health. Despite its importance in metabolic processes, little is known about the Zn-epigenetic. Thus, the present study aimed to identify the epigenetic variables associated with Zn daily ingestion (ZnDI) and serum Zinc (ZnS) levels in women with and without obesity. Materials and methods: this is a case-control, non-randomized, single-center study conducted with 21 women allocated into two groups: Control Group (CG), composed of 11 women without obesity, and Study Group (SG), composed of 10 women with obesity. Anthropometric measurements, ZnDI, and ZnS levels were evaluated. Also, the leukocyte DNA was extracted for DNA methylation analysis using the 450k Illumina BeadChips. The Epigenetic Clock was calculated by the Horvath method. The ChAMP package selected the Differentially Methylated Regions (DMRs). Results: The SG had lower ZnS levels than the CG. Moreover, in SG, the ZnS levels were negatively associated with the epigenetic age acceleration. The DMR analysis revealed 37 DMRs associated with ZnDI and ZnS levels. The DMR of the PM20D1 gene was commonly associated with ZnDI and ZnS levels and was hypomethylated in the SG. Conclusion: Our findings provide new information on Zn's modulation of DNA methylation patterns and bring new perspectives for understanding the nutriepigenetic mechanisms in obesity.